FOUR STRATEGIES IN TEACHING SPEAKING DURING COVID -19 PANDEMIC AT SMA N 04 PALEMBANG - Rahayu, Aprilia Sari; Eryansyah, Eryansyah; Sitinjak, Margaretha Dinar (English Review: Journal of English Education, 2022)
Teaching and learning activities for speaking at SMA N 04 Palembang were conducted online, as one of the efforts to suppress the spread of Covid-19. The process of teaching and learning speaking online was conducted was through a web-based application and internet network. In situations like this, teachers had a very important role because they were the ones responsible for motivating, guiding, and correcting mistakes made by students when speaking English. Therefore, teachers of this school had to think critically and use appropriate strategies to ensure that the teaching process during online learning ran well. The purpose of this study was to describe teacher's strategies of SMA N 04 Palembang in teaching speaking during the current Covid-19 Pandemic. This study used a qualitative narrative inquiry method. The participants in this study were four English teachers in SMA N 04 Palembang. Data collection techniques in this study were observation and interviews. The results showed that the teachers at SMA N 04 Palembang used four strategies, namely roleplaying, storytelling, discussion and reporting. Thus, from those strategies, roleplaying and storytelling seemed to be the most commonly used as they were considered to improve students’ English speaking skills during online learning.